2019
DOI: 10.15171/joddd.2019.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a fluoride-releasing fissure sealant and a conventional fissure sealant on inhibition of primary carious lesions with or without exposure to fluoride-containing toothpaste

Abstract: Background. Fluoride-releasing capacity has been added to fissure sealants to benefit from the positive anticariogenic effects of both sealants and fluoride. This comparative research investigated the inhibitory effects of conventional and fluoridereleasing fissure sealants on initial lesions with or without exposure to fluoride toothpaste. Methods. Cavities were prepared on buccal surfaces of 24 premolar teeth which were randomly divided into three groups. In the cavities of the first group, a fluoride-relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…However, studies have been actively developing and investigating new bioactive materials and their anti-cariogenic effects and mechanical properties [ 22 , 23 , 29 , 35 , 36 ]. Only a few studies have studied the performance of recently introduced bioactive resin-based sealants.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have been actively developing and investigating new bioactive materials and their anti-cariogenic effects and mechanical properties [ 22 , 23 , 29 , 35 , 36 ]. Only a few studies have studied the performance of recently introduced bioactive resin-based sealants.…”
Section: Introductionmentioning
confidence: 99%
“…Sadrabad et al [ 22 ] observed that fluoride released from sealants is not only effective in inhibiting tooth decay, but its remineralization capacity exceeds that of fluoride released from toothpaste.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used different methodologies to compare the application of ionomeric and resinous materials to pits and fissures in an attempt to prevent demineralization. [17,[20][21][22] Therefore, in this study, a cavity preparation was performed to simulate the conditions of pits and fissures and the Knoop microhardness test was carried out to assess demineralization around the preparation margins after 48-hour biofilm formation. Knoop microhardness has been widely used for this purpose [18,23,24] and the S. mutans biofilm metabolic activity test, which can simulate oral conditions, has been used to replace cyclic pH.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not evaluate demineralization immediately after placement of the material, as in other studies. [17,39]…”
Section: Discussionmentioning
confidence: 99%